Hepatectomy for hepatocellular carcinoma larger than 10 cm: preoperative risk stratification to prevent futile surgery. Issue 7 (16th May 2015) - Lim, Chetana; Compagnon, Philippe; Sebagh, Mylène; Salloum, Chady; Calderaro, Julien; Luciani, Alain; Pascal, Gérard; Laurent, Alexis; Levesque, Eric; Maggi, Umberto; Feray, Cyrille; Cherqui, Daniel; et al.
Abstract Objectives Appropriate patient selection is important to achieving good outcomes and obviating futile surgery in patients with huge (≥10 cm) hepatocellular carcinoma (HCC). The aim of this study was to identify independent predictors of futile outcomes, defined as death within 3 months of surgery or within 1 year from early recurrence following hepatectomy for huge HCC. Methods The outcomes of 149 patients with huge HCCs who underwent resection during 1995–2012 were analysed. Multivariate logistic regression analysis was performed to identify preoperative independent predictors of futility. Results Independent predictors of 3‐month mortality (18.1%) were: total bilirubin level >34 μmol/l [P = 0.0443; odds ratio (OR) 16.470]; platelet count of <150 000 cells/ml (P = 0.0098; OR 5.039), and the presence of portal vein tumour thrombosis (P = 0.0041; OR 5.138). The last of these was the sole independent predictor of 1‐year recurrence‐related mortality (17.2%). Rates of recurrence‐related mortality at 3 months and 1 year were, respectively, 6.3% and 7.1% in patients with Barcelona Clinic Liver Cancer (BCLC) stage A disease, 12.5% and 14% in patients with BCLC stage B disease, and 37.8% (P = 0.0002) and 75% (P = 0.0002) in patients with BCLC stage C disease. Conclusions According to the present data, among patients submitted to hepatectomy for huge HCC, those with a high bilirubin level, low platelet count and portal vein thrombosis are at higher risk for futile surgery. The presence of portal vein tumour thrombosis should be regarded as a relative contraindication to surgery.